Modelling of high‐power IGBT module short‐circuit operation and current distribution by a behavioural model. Issue 14 (1st November 2016) - Musikka, Tatu; Smirnova, Liudmila; Niemelä, Markku; Silventoinen, Pertti; Pyrhönen, Olli
Abstract : This study presents current distribution modelling methods for a dual pack insulated‐gate bipolar transistor (IGBT) module, which is operating under short‐circuit conditions. The parasitic components of the commutation circuit current conductors and the internal busbars of the module are modelled by a three‐dimensional finite‐element method and the IGBT chips by a behavioural semiconductor model. The lumped IGBT chip model is characterised by using datasheet information only and without fine tuning of the model parameters. The mechanical dimensions of the IGBT module and the experimental setup are used to define the parasitic components for the commutation circuit. The model accuracy is investigated by comparing simulated dynamic and steady‐state short‐circuit parameters with experimental ones. Furthermore, uneven current distribution in the module main current terminals is observed in the simulations, and the behaviour is verified by experimental tests. The phenomenon may cause additional mechanical and electrical stresses in the device for instance because of thermal expansion and current couplings. The results show that the proposed methods are suitable to model the IGBT short‐circuit behaviour and current distribution inside the module and can be used for example in the virtual design of power electronic inverter or switched power supply.